Perestroika (1987–1999) - Stegaylo, Vladimir; Buynov, Alexey; Zhukovsky, Nikolai; Demkov, Sergey; Sherstova, Natalya (project baikal, 2015)
After Brezhnev’s death, starting from 1983, there were troublesome times in Russia. At first the senile secretaries general came and passed away, making ‘a funeral parade’, and then Gorbachev’s perestroika started. The wind of change shook all foundations of usual mode of life. The economic collapse of the 1990s brought in all forms of wild capitalism. The profession was not able to feed any more. Even recognized masters of architecture had to breed poultry in the country and return bottles to feed their families. But we weathered those bad times. Some of us quitted the profession; others remained, in spite of all non-payments, unemployment and other antics of the primary accumulation epoch…
Keywords: troublesome times; perestroika; unemployment; primary accumulation of capital